Marketing Strategy to Increase Sales Volume In Juno Fried Chicken MSMEs, Natar District, South Lampung Regency - Aidah, Aprivia; Riswan (Journal of Advances in Accounting, Economics, and Management, 2025)
Micro, Small, and Medium Enterprises (MSMEs) face challenges like fluctuating consumer demand and intense competition in the food industry. This study explores how Juno Fried Chicken uses product innovation to address these issues and boost sales. The research aims to identify factors behind inconsistent revenue and suggest strategies for improving market position. Using a qualitative approach, including interviews, observations, and document analysis, a SWOT analysis was conducted to evaluate the company’s strengths, weaknesses, opportunities, and threats. Findings show that while Juno Fried Chicken benefits from product innovation and digital marketing, challenges like low brand visibility and operational inefficiency remain. The study recommends improving digital marketing, expanding delivery services, and enhancing operational capacity to strengthen competitiveness and ensure long-term growth.